2017
DOI: 10.1155/2017/5635640
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative C-Reactive Protein as a Risk Factor for Postoperative Delirium in Elderly Patients Undergoing Laparoscopic Surgery for Colon Carcinoma

Abstract: Background Postoperative delirium (POD) is a very common complication in operative disciplines, especially in those elderly patients after cardiac surgery. This study aimed to investigate the relationship between C-reactive protein (CRP) and POD in elderly patients undergoing laparoscopic surgery for colon carcinoma. Methods 160 elderly patients scheduled to undergo selective laparoscopic surgery for colon carcinoma were prospectively recruited in this present study. The preoperative demographic and medical ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 26 publications
2
47
2
Order By: Relevance
“…These findings add to the limited number of studies investigating the predictive value of pre‐operative CRP for POD and cognitive decline. Our results are consistent with those reported by the SAGES study group and those of Xiang et al, who also observed higher CRP levels before surgery in elderly patients developing POD after non‐cardiac surgery. These recent studies along with our findings represent emerging evidence for the use of CRP as a biomarker to risk stratify patients before surgery.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings add to the limited number of studies investigating the predictive value of pre‐operative CRP for POD and cognitive decline. Our results are consistent with those reported by the SAGES study group and those of Xiang et al, who also observed higher CRP levels before surgery in elderly patients developing POD after non‐cardiac surgery. These recent studies along with our findings represent emerging evidence for the use of CRP as a biomarker to risk stratify patients before surgery.…”
Section: Discussionsupporting
confidence: 93%
“…However, reasonable evidence supports the use of CRP for risk stratification of surgical patients. Both Dillon and Xiang found elevated CRP levels before surgery to be predictive for POD. This was confirmed in a more recent meta‐analysis by Liu et al who identified an association of pre‐operative CRP with POD in non‐cardiac patients compared to cardiac surgery patients.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to those of elective hip surgery patients, the preoperative serum levels of CRP in patients with hip fracture can not be considered a predisposing risk factor at baseline. This could explain that elevated preoperative serum CRP levels are found as predisposing risk factors for postoperative delirium in cardiovascular, coloncarinoma, and elective orthopedic surgery 13,19,41 but not in patients undergoing surgery for hip fracture. 12,[21][22][23][24] It has been proposed that delirium that develops in the hours after surgery can be distinguished from delirium that develops after a free interval of 24 to 72 hours after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The operational definition describing delirium is applied to POD when the clinical manifestations of delirium appear after surgical operation. Delirium refers to acutely altered and fluctuating mental status with signs of altered level of consciousness and inability to maintain attention [12][13][14][15][16][17][18][19][20][21][22]. This condition cannot be explained by any other neurocognitive disorder and has a sudden onset.…”
Section: Definitionmentioning
confidence: 99%
“…Surgery-specific risk factors that put patient body at more stressed state include the followings: invasive preoperative preparation (e.g. mechanical enema, nasogastric tube insertion) [13,15], blood transfusions [12,19], greater blood loss [19], crystalloid infusions [19,20], cardiovascular events [20,22], longer operation hours [19], longer hours spent to recover from general anesthesia [18], inflammatory response mediated by proinflammatory cytokines [15], delayed feeding [15], and postoperative analgesic administration [12,15].…”
Section: Pathophysiologymentioning
confidence: 99%